A study on customer perception & product quality of organized retail outlets with special reference to pothys in madurai - S, KUMAR; S, VARADARAJ (Journal of Management and Science, 2013)
The purpose of this study is to identify the customer perception and product quality of apparel consumer in apparel product categories, in the context of the evolving organized retail industry in India. With the help of customer perception of retail outlets increase their sale and provide total customer satisfaction. These Retail Outlets increase the India as well as in all over the world. The term customer perception refers to the perception that customers display in searching for purchasing, using, evaluating and disposing of products and services that they will expect will satisfy their needs. The paper attempts to correlate the distinct store features as perceived by respondents with the true motivations of various customers in perception and product quality of organized outlets. In the process it provides insight of various attributes influencing the customer of an average Indian customer. The sample size used in the study consists of 100 respondents of apparel retail outlets. The study conducted is analytic in nature aimed at finding out the customer perception and product quality of apparel retail outlets. The conclusion of the study was that the suggestions were the increase after having analysed interpreted the findings. It is concluded that customer perception and product quality of retail outlets play a significant role to enhance the perception with customers and provide total customer satisfaction. It signifies that several factors, then after set hypothesis to accept and reject hypothesis. The study for future study is that is to feel up form with customers sensuously and take interview of customer, who walking in the shop floor of Retail Outlet. And to know in-depth psychology and perception of customers, it will give better result for study.